(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article analyzes the content and modern approaches to mathematics education in primary schools. The effectiveness of interactive methods, ICT (information and communication technologies), STEAM education, differentiated approach, problem-based learning and game technologies in the process of teaching mathematics is scientifically highlighted. Ways to develop students’ logical thinking, increase the effectiveness of learning and increase their interest in mathematics in primary education are shown.